Lightening the workload - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
In order to sow as soon as possible after the first rains, farmers must be able to prepare their fields quickly. Two new pieces of equipment for animal traction which would speed up this work have recently been developed by the Centre for Research...